Pendaftaran Merek Dagang dengan Menggunakan Kata Umum - Stevi Josua Leimena; Merry Tjoanda; Nancy Silvana Haliwela (Faculty of Law, Universitas Pattimura, 2023)
Introduction: A mark cannot be registered if it is a common name and/or a symbol of public property but in trade there is circulation of a mark using the general word.Purposes of the Research: To analyze and explain how the registration of trademarks that use common words and the legal consequences for trademarks that use common words as marks. Methods of the Research: The research method used is normative juridical research, the type of research is descriptive analytical. The sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials used in this research is through literature study. The analysis of legal materials is descriptive qualitativ.Results of the Research: The results showed: 1). Procedures and legal rules for trademark registration are regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications and Regulation of the Minister of Law and Human Rights Number 67 of 2016 concerning Registration of Marks and Regulation of the Minister of Law and Human Rights Number 12 of 2021 concerning Changes On the Regulation of the Minister of Law and Human Rights Number 67 of 2016 concerning Trademark Registration. 2) The legal consequences for trademarks that use the Common Name as a Mark can be seen in Article 20 of Law Number 20 of 2016 and Article 16 Letter (f) of the Regulation of the Minister of Law and Human Rights Number 12 of 2021 concerning Amendments to the Regulation of the Minister of Law And Human Rights Number 67 of 2016 concerning Mark Registration is by carrying out law enforcement efforts in the form of